Vitás és vitatott gazdasági kérdések az Osztrák-Magyar Monarchia felbomlása után - Szávai, Ferenc (Közép-Európai Közlemények, 2010)
After the breakup of the Austro-Hungarian Monarchy, rebuilding the Hungarian economy became a primary objective, which was eventually carried out with a loan from the League of Nations. It was highly debated whether it was necessary, and whether it was spent appropriately. At the period there was an ongoing dispute between Hungary and Austria over the debt obligation ensuing from the common wealth of the Austro-Hungarian Monarchy, and the period at which the optant lawsuits happened. Szterényi József played an important role in all these controversial matters, his name and activities connecting together the above problems.